Proteostasis and unfolded protein response dynamics in human neuron/mouse glia co-cultures reveal a cell-specific maturation response - Lea A. Barny; Sarah K. Garcia; Aiden J. Houcek; Burak Uzay; Minsoo Kim; Ege T. Kavalali; Lars Plate (Proceedings of the National Academy of Sciences, 2026)
Proteostasis, or protein homeostasis, is a tightly regulated network of cellular pathways essential for maintaining proper protein folding, trafficking, and degradation. Neurons are particularly vulnerable to proteostasis collapse due to their postmitotic and long-lived nature and thus represent a unique cell type to understand the dynamics of proteostasis throughout development and maturation. Here, we utilized a dual-species co-culture model of human excitatory neurons and mouse glia to recapitulate and investigate cell type–specific, maturation-related changes in the proteostasis network using data-independent acquisition LC–MS/MS proteomics. We quantified branch-specific unfolded protein response (UPR) activation by monitoring curated effector proteins downstream of the ATF6, IRE1/XBP1s, and PERK pathways, enabling a comprehensive, unbiased evaluation of UPR dynamics during in vitro neuronal maturation between 30 d and 60 d. Species-specific analysis revealed that mature neurons largely preserved proteostasis, although they showed some signs of collapse, primarily in endoplasmic reticulum (ER)-to-Golgi transport mechanisms. However, these changes were accompanied by upregulation of proteostasis-related machinery and activation of the ATF6 branch, as well as maintenance of the XBP1s and PERK branches of the UPR over time. In contrast, glia exhibited broad downregulation of proteostasis factors and UPR components, independent of neuronal presence. Furthermore, we quantified stimulus-specific modulation of select UPR branches in matured neurons exposed to pharmacologic ER stressors. These findings highlight distinct, cell-type-specific stress adaptations during in vitro maturation and provide a valuable proteomic resource for dissecting proteostasis and UPR regulation in human neurons.